Pilih Piring Sehat Kelolah Diabetes Dengan Isi Piringku Dikelurahan Ponorogo Rt 04 Kecamatan Lubuklinggau Utara II - Sari, Nanda Permata; Oktapiani, Wesi; Anggraini, Aisyah; Wiwik, Wiwik; Ramasic, Revani; Handayani, Tita Septi; Rohani, Tuti; Azissah, Danur (Jurnal Dehasen Mengabdi, 2025)
Background: The diabetes diet is an eating pattern that involves consuming moderate amounts of healthy food at regular times. Understanding how the food we eat is very important in preventing diabetes. Therefore, diet is one of the two main ways to prevent diabetes. You can easily follow the suggestions in the contents of my plate, which are instructions from the Ministry of Health for the amount of food we eat. portions of each food in one dish.Objective: Increase the understanding of people with diabetes/high risk about healthy eating patterns using the principle of what's on my plate and the community can arrange a healthy plate menu after the demonstration Method: The method used in this community service program is health promotion using counseling methods. The media used is leaflets.Results: The results of the case study show that after arranging the contents of my plate, respondents were able to apply the principles of balanced nutrition to the contents of my plateConclusion: The results of the case study show that before being given how to arrange the contents of my plate, the client did not know how to arrange the contents of my plate for DM/high risk clients. After being given how to arrange the contents of my plate for diabetes, the client was able to apply it.